Hydrodynamic electrochemistry: design for a high-speed rotating disk electrode. - Banks, C; Simm, A; Bowler, R; Dawes, K; Compton, R (2005)
We report a novel gas-driven high-speed rotating disk electrode (HSRDE). The HSRDE when immersed in an aqueous solution rotates at approximately 650 Hz, generating laminar flow resulting in a diffusion layer, under steady-state conditions, of thickness approximately 2 microm. The use of high-pressure gas to drive the rotator offers significant improvement in electrical noise as compared to conventional mechanically driven devices. The electroanalytical utility of the HSRDE was exemplified by the anodic stripping voltammetry of arsenic(III) at a gold working electrode. The charge under the arsenic stripping peak was found to increase by more than 1 order of magnitude under the enhanced mass transport regime at the HSRDE in comparison to that seen under quiescent conditions.